1992
DOI: 10.2105/ajph.82.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a self-help dietary intervention in a primary care setting.

Abstract: BACKGROUND. Dietary intervention to reduce fat consumption and increase fiber consumption has been recommended by the National Cancer Institute, but there is little evidence concerning the effectiveness of self-help materials. The purpose of this study was to evaluate such self-help materials, introduced by a nurse in a primary care setting. METHODS. A randomized controlled trial involving 242 subjects was conducted in two primary care clinics in Chapel Hill, NC, in 1987. Changes in fat and fiber consumption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…Autonomy/responsibility for food-related behaviors was considered as a possible mediator based on previous work of Beresford et al [12,13] who found in their study of primary care patients that autonomy/responsibility was strongly related to F&V change. We had hypothesized that project activities and education might increase participants' level of food-related responsibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autonomy/responsibility for food-related behaviors was considered as a possible mediator based on previous work of Beresford et al [12,13] who found in their study of primary care patients that autonomy/responsibility was strongly related to F&V change. We had hypothesized that project activities and education might increase participants' level of food-related responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial measures were knowledge/awareness of the 5 A Day recommendation, selfefficacy, stage of readiness to increase F&V, and autonomy/ responsibility for food-related behaviors. These constructs were selected based on prior research indicating that they were potential determinants of dietary behavior [3,[10][11][12][13]. For example, the national 5 A Day Baseline Survey conducted in 1991 indicated that knowledge of the number of F&V servings recommended each day accounted for a significant portion of the variance in consumption [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research focused on reducing dietary fat intake, participants with complete autonomy (independent responsibility and control) regarding food choice made larger changes attributable to intervention. 33 The role of autonomy in increasing fruit and vegetable consumption has not been examined before. Five sites included a set of three questions on autonomy to explore its possible link to fruit and vegetable behavior.…”
Section: Self-efficacymentioning
confidence: 99%
“…'5 Further, it has been found that many people prefer self-help materials as an approach to the promotion of changes in health behavior. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The importance of these lowintensity interventions lies in their potential to affect large numbers of the population.7 Although the resulting change in behavior may be quite small at the individual level, its impact at the population level can be quite dramatic.…”
Section: Introductionmentioning
confidence: 99%